PELAKSANAAN KERJASAMA SISTER CITY PEMERINTAH KOTA BANDUNG (INDONESIA) DENGAN KOTA PETALING JAYA (MALAYSIA) - Evan R; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The process of globalization encouraged the emergence of new actors in international cooperation, namely the local government with one of the forms of sister city international cooperation. Bandung is one of the cities that utilizes this collaboration to optimize its regional potential with the City of Petaling Jaya, Malaysia since 2015. This research aims to explain why Bandung wants to do a sister city collaboration with Petaling Jaya. The research method used in this study is descriptive-qualitative which uses primary data based on interviews and secondary data such as books, journals, and several other sources. The perspective that I use is a pluralism perspective with the level of analysis of the nation state and using the theory of international cooperation. The result of this research is to tell the reason Bandung collaborated with Petaling Jaya because of several factors such as the economy sector because it is a well-known shopping tourist destination, Petaling Jaya is also a city of education as well as Bandung so that both have extensive cooperation opportunities, have good urban planning and tourism advanced. So with these factors can increase Bandung tourism industry. Keywords: Sister City, Cooperation, Local Potential